Potential of Allium cepa in thromboembolism in Ulcerative Colitis in Rats - Ige, Serah Funke; Adekola, Aminat Aderayo (Journal of Drug Delivery and Therapeutics, 2021)
Colitis and coagulation influence each other and patients with colitis have been reported to have an increased risk of thromboembolic events. Allium cepa has been reported to have anti-coagulative activity and anti-inflammatory activity. This research was carried out to investigate the effect of Allium cepa on coagulation changes in colitisTwenty eight rats weighed 180 ± 20g were used for this study.  They were divided into four groups; Control group, Colitis group, Allium Cepa + Colitis group and Allium Cepa group. Allium Cepa + Colitis group and Allium Cepa were given 1ml/100g body weight of Allium cepa extract daily for 28days orally. Colitis was induced by a single dose of intra-rectal administration of 1ml/100g body weight of 6% acetic acid. Forty eight hours after the colitis induction, blood was taken by cardiac puncture for clotting time test, Prothrombin time (PT), Partial thromboplastin time with kaolin test (PTT.K), platelet count, Calcium ion and Potassium ion test. Calcium ion was significantly decreased while potassium ion, platelet count, significantly increased and partial thromboplastin time shortened in colitis animals when compared with control. Calcium ion, potassium ion, platelet count and partial thromboplastin time showed no significant difference in Allium Cepa + Colitis group when compared with control.  It can be concluded that Allium cepa has potential to reduced the risk of thromboembolism in colitis Keywords: Colitis, Allium cepa, thromboembolism